1993
DOI: 10.1099/0022-1317-74-10-2071
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B1-induced murine myositis: no evidence for viral persistence

Abstract: The persistence of coxsackievirus B1 in the muscles of mice with coxsackievirus Bl-induced chronic myositis was investigated. Neonatal CD1 Swiss mice were inoculated with a myositis-causing variant of coxsackievirus B1 (Tucson strain). Hamstring muscle samples of diseased mice obtained at various times after inoculation were examined for the presence of infectious virus, viral RNA and histological abnormalities. Viral RNA was detected up to 4 weeks after initiation of infection, whereas virus could be isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Muscles were paraffin-embedded and sectioned at 6 /¿m. In a previous study we found that most extensive inflammatory and myopathic changes occurred in hamstring muscles, in agreement with previous reports (19,38) and with the fact that these muscles were the most atrophic on macroscopy (27,32). W e also dem on strated that the histological changes (m ononuclear cell infiltra tion, muscle fiber necrosis, central nuclei, fiber atrophy) were evenly distributed over the w hole length of a muscle (2 0 ), and that cross section areas of ham string muscles at 2 weeks did not differ significantly from those at 4 weeks (19).…”
Section: Histologicai Examinationsupporting
confidence: 80%
“…Muscles were paraffin-embedded and sectioned at 6 /¿m. In a previous study we found that most extensive inflammatory and myopathic changes occurred in hamstring muscles, in agreement with previous reports (19,38) and with the fact that these muscles were the most atrophic on macroscopy (27,32). W e also dem on strated that the histological changes (m ononuclear cell infiltra tion, muscle fiber necrosis, central nuclei, fiber atrophy) were evenly distributed over the w hole length of a muscle (2 0 ), and that cross section areas of ham string muscles at 2 weeks did not differ significantly from those at 4 weeks (19).…”
Section: Histologicai Examinationsupporting
confidence: 80%
“…Total RNA was isolated from 100 l of cellular lysates obtained from the 8-h time point of the growth curve, using a single extraction procedure with guanidinium thiocyanate-phenol-chloroform (9). Mutated RNA was PCR amplified, using a poly(T) primer and a primer located in the 3D coding region (5Ј-GTTGTTTGACCCTCCCCGCG-3Ј; nt 7241 to 7260) as described previously (48). The resultant 179-bp reverse transcriptase PCR products were purified by low-melting-point agarose gel electrophoresis and sequenced as described above.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was isolated from 100 l of virus stock by a single extraction procedure with guanidinium thiocyanate-phenol-chloroform according to the method described by Chomczynski and Sacchi (11). Reverse transcription of RNA and amplification of cDNA by PCR with forward primer 5Ј-GCAATGGAACAGGGAGTGAAG GACTATGTGGA-3Ј (nt 3733 to 3765) and reverse primer 5Ј-TTGGGATGGC GCGCTCTGCTC-3Ј (nt 4231 to 4251) were performed as described previously (42). The resulting 519-bp PCR products were purified by low-melting-point agarose gel electrophoresis.…”
Section: Cells and Virusesmentioning
confidence: 99%